O que e como ensinar: proposta curricular, materiais didáticos e prática de ensino nas escolas públicas estaduais em São Paulo (2008-2009) - Boim, Thiago Figueira (2010)
In order to systematize what should be taught and how to be taught, the Sao Paulo government set up its own education system. By resolution number 92 of the Department of Education, on 19 December 2007, set up guidelines for the curriculum Elementary and Middle schools in São Paulo State. The Proposal curriculum of the State of Sao Paulo based on a uniform curriculum with materials themselves - the student's notebook and notebook professor - developed for all levels of education. The aim is to proposed curriculum, achieve the goals of quality education launched 2010, the current management of the government of São Paulo. The Proposal curriculum of the State of Sao Paulo based on a uniform curriculum with materials themselves - the student's notebook and notebook professor - developed for all levels of education. The aim is to proposed curriculum, achieve the goals of quality education launched 2010, the current management of the government of Sao Paulo. That order was received by teachers teaching materials? What place occupies the textbook in the classroom? Is only one teacher performer? At this rate, the survey gives evidence in short-term results of the first project "Sao Paulo faz Escola", as well as the placement of teachers on the new changes